2018
DOI: 10.1111/ane.12959
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and cardiorespiratory fitness in persons with multiple sclerosis

Abstract: The findings suggest that BMI has a negative impact on CRF in pwMS, with a marked reduction in CRF for those classified as obese compared to those in the normal and overweight category.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…Obesity predicts adverse clinical outcomes and treatment responses in rheumatoid arthritis, systemic lupus erythematosus and psoriasis, [88][89][90] worsens functional capacity in systemic sclerosis, 91 increases the prevalence and worsens the severity of asthma, 92 has deleterious effects in inflammatory bowel disease and multiple sclerosis, 93,94 and contributes to the progression of diabetes, non-alcoholic steatohepatitis and chronic kidney disease. [95][96][97] By acting as a broad accelerant of systemic inflammation, obesity potentiates the likelihood of heart failure (particularly HFpEF) in patients who are already prone to its development.…”
Section: Obesity As a Link Between Systemic Inflammation And Metabolimentioning
confidence: 99%
“…Obesity predicts adverse clinical outcomes and treatment responses in rheumatoid arthritis, systemic lupus erythematosus and psoriasis, [88][89][90] worsens functional capacity in systemic sclerosis, 91 increases the prevalence and worsens the severity of asthma, 92 has deleterious effects in inflammatory bowel disease and multiple sclerosis, 93,94 and contributes to the progression of diabetes, non-alcoholic steatohepatitis and chronic kidney disease. [95][96][97] By acting as a broad accelerant of systemic inflammation, obesity potentiates the likelihood of heart failure (particularly HFpEF) in patients who are already prone to its development.…”
Section: Obesity As a Link Between Systemic Inflammation And Metabolimentioning
confidence: 99%
“…In addition, the loss of muscle is directly associated with an increase in body fat in MS patients [ 11 ]. This also causes a rise in inflammation [ 12 ], resulting in a loss in respiratory capacity and fatigue [ 13 ]; therefore, the patient’s disability and the progression of the disease are increased [ 14 ]. In addition, an increase in body fat is associated with a greater expression of the butyrylcholinesterase enzyme (BuChE) in blood serum [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Contrarily, Pilutti et al (10) found no significant difference in various mobility outcomes, such as walking speed and endurance, based on the BMI status. Sebastião et al (12) showed that patients with MS and obesity have lower cardiorespiratory fitness than overweight and non-obese groups. Studies that investigate the relationship between the lower limb functions and obesity in people with MS have presented mixed results.…”
Section: Introductionmentioning
confidence: 99%